“May” in Africa - (:unkn) unknown (My University, 2018)
Only recently have scholars started to examine African student movements. The case of the Senegalese May 68 is the most well known example. The book Étudiants africains en mouvements : contribution à une histoire des années 68, based on papers presented at an international conference in 2015, presents other student movements that developed between 1960 and 1980 in 11 mostly French-speaking countries, as well as in a few Anglophone ones.
Keywords: African Research